Solving vector interval-valued optimization problems with infinite interval constraints via integral-type penalty function. (2nd December 2022) - Qian, Xinqiang; Wang, Kai-Rong; Li, Xiao-Bing
Abstract : This paper aims at establishing necessary optimality conditions for a nondifferentiable multiobjective interval-valued optimization problem with infinite interval-valued constraints, and then deriving the equivalence of the weakly LU efficient solution between the primal optimization problem and its integral-type penalized optimization problem, which provides us supporting theories when we solve this kind of optimization problem by means of penalty function method. The equivalence of the weakly LU efficiency is established under some suitable conditions. Some examples are provided to illustrate the advantages of our results in some cases.